2017
DOI: 10.3389/fncir.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

Sparse and Specific Coding during Information Transmission between Co-cultured Dentate Gyrus and CA3 Hippocampal Networks

Abstract: To better understand encoding and decoding of stimulus information in two specific hippocampal sub-regions, we isolated and co-cultured rat primary dentate gyrus (DG) and CA3 neurons within a two-chamber device with axonal connectivity via micro-tunnels. We tested the hypothesis that, in these engineered networks, decoding performance of stimulus site information would be more accurate when stimuli and information flow occur in anatomically correct feed-forward DG to CA3 vs. CA3 back to DG. In particular, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…The MEA60 amplifier recorded electrophysiological activity at constant temperature of 37°C and in a humidified atmosphere of 5% CO 2 and 9% O 2 (custom gas mixture, balance N 2 ; Airgas, Santa Ana, CA). Our previous works with two chambers (Brewer et al 2013; Poli et al 2017a) demonstrated not only excellent neuron survival equivalent to the original cell plating densities, but also strong axonal polarity consistent with the hippocampal anatomy. Polarity was determined from delay times as an axonal spike traveled from one electrode to the next in a micro-tunnel.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The MEA60 amplifier recorded electrophysiological activity at constant temperature of 37°C and in a humidified atmosphere of 5% CO 2 and 9% O 2 (custom gas mixture, balance N 2 ; Airgas, Santa Ana, CA). Our previous works with two chambers (Brewer et al 2013; Poli et al 2017a) demonstrated not only excellent neuron survival equivalent to the original cell plating densities, but also strong axonal polarity consistent with the hippocampal anatomy. Polarity was determined from delay times as an axonal spike traveled from one electrode to the next in a micro-tunnel.…”
Section: Methodssupporting
confidence: 59%
“…Furthermore, the micro-tunnels allowed robust axonal connection between chambers because of a strong dependence of the network functional strength of connectivity on the number of tunnels inputs (Pan et al 2015, DeMarse et al 2016). We applied paired-pulse stimulation at 22 electrode sites in this model system to promote native feed-forward information transmission, facilitating evoked network responses that correlated between the source and the axons in the tunnels, as well as between the transmitted axonal activity and target subregion (Poli et al 2017a). Pattern separation can be inferred when inputs are more similar than outputs.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, new methods of neuroengineering have been developed to control the position of cells and direction of axon and dendrite growth (le Feber et al, 2015;Na et al, 2016;Renault et al, 2016). Recently, it has been shown that the main feature of functional network topology as unidirectional synaptic connectivity between cell clusters can also be engineered using microfluidic technology (Gladkov et al, 2017;Poli et al, 2017;Forró et al, 2018). Being implanted in the damaged brain, such tools of network structure manipulation allow one to mimic brain areas, which are involved in reflex activity, pattern retrieval in multilayered unidirectional network (Brewer et al, 2013;Poli et al, 2017) for neural tissue recovery from brain injury (Shimba et al, 2019).…”
Section: Living Neural Network: Biological Side Of Neural Integrationmentioning
confidence: 99%
“…Recently, it has been shown that the main feature of functional network topology as unidirectional synaptic connectivity between cell clusters can also be engineered using microfluidic technology (Gladkov et al, 2017;Poli et al, 2017;Forró et al, 2018). Being implanted in the damaged brain, such tools of network structure manipulation allow one to mimic brain areas, which are involved in reflex activity, pattern retrieval in multilayered unidirectional network (Brewer et al, 2013;Poli et al, 2017) for neural tissue recovery from brain injury (Shimba et al, 2019). Next, it could be combined with an array of non-invasive planar microelectrodes, which provide spiking activity registration and stimulation of isolated or multiple neurons.…”
Section: Living Neural Network: Biological Side Of Neural Integrationmentioning
confidence: 99%
“…chain-like and feedforward networks) have been experimentally used to investigate how the layout influences the spontaneous activity. Furthermore, these networks have the capability of self-organizing forming spontaneous connections among the modules with the possibility to study how dynamics changes compared to uniform networks and to networks composed of well-known anatomical layouts [59]. Multi-modular networks can be electrically stimulated with the possibility to have a better control over the evoked activity, thanks to the structural and functional confinement ensured by the neuronal circuits.…”
Section: Network Events: Identification and Similaritymentioning
confidence: 99%